SPRITUAL ENTEPRENEURSHIP DALAM PEMBERDAYAAN EKONOMI UMAT: Studi terhadap Tarekat Idrisiyah Pageningan Tasikmalaya - Dede Aji Mardani (al-Afkar, Journal For Islamic Studies, 2019)
This research aims to determine the conduction model between the worship and rite vertically and the effect on the economic empowerment of communities sustainaglely which aimed to improve people's viable living, self-sufficient in the competitive sector of the primary sectors of public life. These results indicate that the level of spirituality and leadership of Jemaah congregation widely impact and gain the sympathy of the local Muslim community and where the congregation stands branding company. It shows a positive correlation where the concept of spirituality and substance with the spirit of making efforts and empowering people to create business opportunities or employment and independence by the expansion of business areas that can provide additional income, poverty reduction, investment unemployment reduction, increased savings and increased purchasing power that will have an impact on sustainable economic growth in accordance with the mission of SDGs. So with the spirit of worship or rite high will increase the sense of caring, utility mastery of economic sectors by the Order Idrisiyah